Adipose Tissue CTGF Expression is Associated with Adiposity and Insulin Resistance in Humans. Issue 6 (19th April 2019) - Yoshino, Jun; Patterson, Bruce W.; Klein, Samuel
Abstract : Objective: Connective tissue growth factor (CTGF) is an important regulator of fibrogenesis in many organs. This study evaluated the interrelationship among adipose tissue CTGF expression, fat mass, and insulin resistance in humans. Methods: This study examined (1) CTGF gene expression in human subcutaneous preadipocytes before and after inducing adipogenesis; (2) relationships among abdominal subcutaneous adipose tissue CTGF gene expression, body fat mass, and indices of insulin sensitivity, including the hepatic insulin sensitivity index and the hyperinsulinemic‐euglycemic clamp procedure in conjunction with stable isotope glucose tracer infusion, in 72 people who had marked differences in adiposity and insulin sensitivity; (3) localization of CTGF protein in subcutaneous adipose tissue; and (4) effect of progressive (5%, 11%, and 16%) weight loss on adipose tissue CTGF gene expression. Results: CTGF was highly expressed in preadipocytes, not adipocytes. Adipose tissue CTGF expression was strongly correlated with body fat mass and both skeletal muscle and liver insulin sensitivity, and CTGF‐positive cells were predominantly found in areas of fibrosis. Progressive weight loss caused a stepwise decrease in adipose tissue CTGF expression. Conclusions: It was concluded that increased CTGF expression is associated with adipose tissue expansion, adipose tissue fibrosis, and multi‐organ insulin resistance in people with obesity.